A educação do campo no fortalecimento do campesinato: da ação dos sujeitos coletivos à construção de uma escola de formação - Magalhães, Sandra Maria Fontenele (2017)
The research developed in this thesis analyzes the Field Education on strengthening of the peasantry in Ceará, based on the experience of the Família Agrícola Dom Fragoso School. For this purpose, it was investigated how was the mobilization of the peasants and their organizations for the development of the Field Education, highlighting the strategies used in this process, in which the struggle for land go along with the struggle for education. The research problem lies in the reality of the advance of capitalism in the countryside, the intensification of social inequalities and the growing precariousness of the education offered to the peasant population. In face of this contradictory and exclusionary reality, the social, union and pastoral movements of the countryside have developed a significant number of educational experiences, aiming to develop an education that promotes the development of the peasant territory, in other words, thinking of associative, cooperative work in the perspective of development of peasant units. The research was structured in two major themes and paradigms of the agrarian question and field education, based on such theoreticians as Martins, Oliveira, Kautsky, Chayanov, Fernandes, Caldart, Castagna, and Freire. In methodological terms, the research was developed based on the following techniques of data collection: semi-structured interview and participant observation. The technical-operational procedures were organized in four axes: 1) bibliographic review; 2) documentary research; 3) field research; and, 4) transcription and analysis of the interviews. The theoretical-methodological assumptions that guide the Field Education and the meanings and senses that the rural school has in the transformation / development of rural settlements. The study points out that Field Education and, more specifically, Família Agrícola Dom Fragoso School has stimulated the reflection and development of teaching in order to promote an understanding of organized class, as well as to develop the sense of belonging to their territories, articulated in the struggle for their land and in their land.